2015
DOI: 10.1002/chem.201501072
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Hydride Catalyzed Highly 1,2‐Selective Pyridine Hydrosilylation

Abstract: Reaction of the calcium hydride complex (DIPPnacnac-CaH⋅THF)2 with pyridine is much faster and selective than that of the corresponding magnesium hydride complex (DIPPnacnac = [(2,6-iPr2 C6 H3 )NC(Me)]2 CH). With a range of pyridine, picoline and quinoline substrates, exclusive transfer of the hydride ligand to the 2-position is observed and also at higher temperatures no 1,2→1,4 isomerization is found. The heteroleptic product DIPPnacnac-Ca(1,2-dihydropyridide)⋅(pyridine) shows fast ligand exchange into homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
2
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 51 publications
2
85
2
6
Order By: Relevance
“…Heating to 60 °C for 15 h lead to the clean rearrangement of 11 to the 1,4‐dihydropyridide derivative 13 [LMg(py) 2 (1,4‐dhp)] (Scheme ). An analogous rearrangement is not possible for 12 under these conditions; a similar observation has previously been noted for other Group 2 metal–hydride systems . The molecular structure of 12 (Figure ) shows a distorted tetrahedrally coordinated Mg 2+ ion, which binds to a terminal κ 1 ‐ N ‐phosphinoamide ligand, a 4‐dimethylamino‐1,2‐dihydropyridide ligand (from formal 1,2‐addition of an MgH unit onto the DMAP pyridine ring), and two neutral, coordinating DMAP molecules.…”
Section: Resultssupporting
confidence: 69%
“…Heating to 60 °C for 15 h lead to the clean rearrangement of 11 to the 1,4‐dihydropyridide derivative 13 [LMg(py) 2 (1,4‐dhp)] (Scheme ). An analogous rearrangement is not possible for 12 under these conditions; a similar observation has previously been noted for other Group 2 metal–hydride systems . The molecular structure of 12 (Figure ) shows a distorted tetrahedrally coordinated Mg 2+ ion, which binds to a terminal κ 1 ‐ N ‐phosphinoamide ligand, a 4‐dimethylamino‐1,2‐dihydropyridide ligand (from formal 1,2‐addition of an MgH unit onto the DMAP pyridine ring), and two neutral, coordinating DMAP molecules.…”
Section: Resultssupporting
confidence: 69%
“…The research groups of Harder,8 Hill,9 Wright,10 and Okuda,11 amongst others,5 have reported main‐group d 0 complexes that are active in stoichiometric and catalytic dehydrocoupling processes; these complexes have contained mostly Group 2 or 13 metals (e.g., Mg, Ca, or Al) and bulky β‐diketiminato or (silyl)amide ligands. Despite this variety of active precatalysts, Group 1 based complexes have remained largely underexplored, which is surprising, since Group 1 precatalysts offer the advantage over Group 2 complexes that they are not involved in Schlenk‐type equilibria,3d though they can engage in aggregation phenomena.…”
mentioning
confidence: 99%
“…1 HNMR (400 MHz, C 6 D 6 ): d = 7.21-7.11( m, 10 H), 7.01 (m, J = 7.4 Hz, 2H), 6.96-6.86 (m, 1H), 6.49 (t, J = 7.1 Hz, 1H), 6.40 (m, J = 7.9 Hz, 2H), 4.95 (s, 1H), 4.10 (s, 2H), 3.26 (hept, J = 6.8 Hz, 4H), 2.96-2.79 (m, 4H), 1.77 (s, 6H), 1.22 (d, J = 6.8 Hz, 12 H), 1.17 (d, J = 6.9 Hz, 12 H), 0.99-0.92 (m, 4H)ppm. 13…”
Section: Synthesis Of Complex ( Dipp Bdi)ca[n(ph)ch 2 Ph]·(thf)mentioning
confidence: 99%
“…[11] Although early main-group-metal catalysis has made substantialp rogress, [12] it is surprising that hitherto imine hydrosilylation has not been reported.T he closest to imine hydrosilylation is the recently described catalytic dearomatization of the C=Nb ond in pyridine by 1,2-selective hydrosilylation using a calcium catalyst. [13] In contrast, magnesium catalysts showed no activity in pyridine hydrosilylation but performed well in its hydroboration. [14,15] In this work we present the first investigations on imine hydrosilylationu sing early main group metal catalysts.…”
Section: Introductionmentioning
confidence: 99%